2022
DOI: 10.13031/ja.14912
|View full text |Cite
|
Sign up to set email alerts
|

Crop Improvement for Circular Bioeconomy Systems

Abstract: HighlightsWe describe and demonstrate a multidimensional framework to integrate environmental and genomic predictors to enable crop improvement for a circular bioeconomy.A model training procedure based on multiple phenotypes is shown to improve predictive skill.The decision set comprised of model outputs can inform selection for both productivity and circularity metrics.Abstract. Contemporary agricultural systems are poised to transition from linear to circular, adopting concepts of recycling, repurposing, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(75 citation statements)
references
References 69 publications
1
74
0
Order By: Relevance
“…At intermediate levels of ET, the interaction of traits as trait networks underpins most of the phenotypic variation. In the presence of these trait interactions and interactions with the environment, we have observed that a CGM can perform better than empirical models (Technow et al 2015, Messina et al 2018, Diepenbrock et al 2022, Messina et al 2022c). Cooper et al (2009) using simulation approaches argued that the benefit of a molecular breeding strategy over phenotypic selection increases with increasing complexity of the genotype and environment system.…”
Section: Models That Predict Emergent Phenotypesmentioning
confidence: 99%
See 4 more Smart Citations
“…At intermediate levels of ET, the interaction of traits as trait networks underpins most of the phenotypic variation. In the presence of these trait interactions and interactions with the environment, we have observed that a CGM can perform better than empirical models (Technow et al 2015, Messina et al 2018, Diepenbrock et al 2022, Messina et al 2022c). Cooper et al (2009) using simulation approaches argued that the benefit of a molecular breeding strategy over phenotypic selection increases with increasing complexity of the genotype and environment system.…”
Section: Models That Predict Emergent Phenotypesmentioning
confidence: 99%
“…At intermediate levels of ET, the interaction of traits as trait networks underpins most of the phenotypic variation. In the presence of these trait interactions and interactions with the environment, we have observed that a CGM can perform better than empirical models (Technow et al 2015, Messina et al 2018, Diepenbrock et al 2022, Messina et al 2022c). Cooper et al…”
Section: Models That Predict Emergent Phenotypesmentioning
confidence: 99%
See 3 more Smart Citations